The structural and organizational aspects of human papillomavirus vaccine affecting immunization coverage in Europe: a systematic review - Ronan Lemwel Valdecantos; Michele Sorrentino; Michelangelo Mercogliano; Vincenzo Giordano; Ugo Trama; Maria Triassi; Raffaele Palladino (BMC Public Health)
Abstract The introduction of HPV vaccinations, that can prevent most prevalent HPV-related cancers of various body districts, is a public health milestone. Despite broad immunization programs, European Health Systems face structural and organizational difficulties that hinder care. This study examined structural and organizational elements that may affect HPV vaccine coverage. We searched numerous databases from January 1, 1995 to May 15, 2023, for literature on HPV immunization research methodologies. Structural and Organizational aspects that cause HPV vaccine concerns in women and men were examined in the outcome evaluations and the research examined vaccination willingness factors. Ottawa, JBI's critical appraisal tool, and Amstar quality assessment assessed bias. A total of 10 articles from 312 studies met the inclusion criteria. Studies were undertaken in Italy, Belgium, England, Switzerland, France, the UK, and Spain. There were also combined-diverse studies in 15 and 27 European countries. Several primary healthcare strategies have increased HPV vaccination rates. These include vaccine procurement and cost-effectiveness, school-based immunization programs, electronic health databases, health professional training, health education and communication, and monitoring and surveillance.